A review on the systems approach for solving the complexity of the environmental problematique of cities in Africa. Issue 1 (1st December 2015) - Chirisa, Innocent; Dirwai, Simbarashe O; Matamanda, Abraham
Abstract: This article is woven to satisfy interlinked objectives of assessing the determinants for successful greening of the city and comparing and contrasting cities in their greening. A cross-sectional review of literature on the role of planning in city greening, the determinant factors for success and limits to this success has been done coupled by case analyses of five cities in the region. To better the situation and future of the African city space, it is imperative to examine the effect of this lack of interactive data and stakeholders' input into urban greening efforts. Unless such a preliminary analysis is done and a model for addressing this, developed, Africa will miss what the industrial city of the eighteenth century missed which eventually led to misery and suffering as cities developed in an unsustainable manner.